Efficacy information influences intention to take COVID‐19 vaccine. Issue 2 (11th July 2021) - Davis, Colin J.; Golding, Matt; McKay, Ryan
Abstract : Objectives: A successful response to the COVID‐19 pandemic requires achieving high levels of vaccine uptake. We tested whether directly contrasting the high efficacy of COVID‐19 vaccines with the lower efficacy of the annual flu vaccine would increase intentions to take a COVID‐19 vaccine. Design: A pre‐registered online study of 481 participants compared four information conditions: (1) no information; (2) COVID‐19 Vaccine Information Only; and COVID‐19 Vaccine Information combined with flu vaccine information suggesting either (3) 60% efficacy or (4) 40% efficacy; we measured COVID‐19 and flu vaccine intentions along with several other vaccine‐related variables. Methods: The Prolific platform was used to recruit 481 UK participants (64% female; aged between 18 and 85 years) who had been pre‐screened to have intermediate levels of vaccine hesitancy. After reading a short text (~200 words) about COVID‐19 vaccines, participants were asked about their vaccination intentions. Results: Providing information about the safety and efficacy of the new COVID‐19 vaccines resulted in vaccination intentions that were, on average, 0.39 standard deviations ( SDs ) higher than those in the no information condition; providing the same COVID vaccine efficacy information in the context of information about flu vaccine efficacy resulted in a further significant increase in vaccination intentions that were 0.68 SD higher than those in the no information condition. This positive contrast effect for the COVID‐19 vaccine was not associated with reduced flu vaccine intentions. Conclusions: Vaccination intentions can be strengthened through a simple messaging intervention that utilizes context effects to increase perceived response efficacy.